Stent-assisted coiling for ruptured anterior choroidal artery aneurysms - Liang He; Weiwei Zhu; Yang Liu; Yulun Huang (Medicine, 2026)
Aneurysms of the anterior choroidal artery (AChA) are rare and pose treatment challenges due to eloquent adjacent anatomy and often complex morphology. This retrospective study evaluates the safety and efficacy of endovascular treatment, particularly stent-assisted coiling (SAC), for acutely ruptured AChA aneurysms, focusing on complications and antiplatelet management. We retrospectively analyzed 29 consecutive patients treated endovascularly within 72 hours of ictus. Patients were stratified by technique (coiling alone, n = 11 vs SAC, n = 18). Within the SAC cohort, 2 antiplatelet regimens were compared: dual antiplatelet therapy (DAPT, n = 7) versus intravenous tirofiban (n = 11). The primary outcome was a favorable clinical outcome (modified Rankin Scale: 0–2) at 6 months. No procedure-related mortality occurred. Periprocedural complication rates were comparable between groups (all P > .05). The overall rate of ischemic events (including intraoperative thrombosis and symptomatic infarction) was 27.8% (5/18) in the SAC group and 9.1% (1/11) in the coiling-alone group. Favorable clinical outcomes at 6 months were achieved in 90.9% of the coiling-alone group and 88.9% of the SAC group (discharge: 72.7% vs 77.8%). After inverse probability of treatment weighting adjustment, SAC was associated with an odds ratio of 1.13 (95% confidence interval [CI]: 0.14–9.09) for favorable outcome. The absolute risk reduction for recurrence was 27.3% (95% CI: 1.0%–53.6%), corresponding to number needed to treat = 3.7 (95% CI: 2.1–14.9). SAC demonstrated a trend toward higher complete occlusion (88.9% vs 63.6%; P = .16) and lower recurrence (0% vs 27.3%; P = .045; fragility index = 1). Within the SAC subgroup, no significant differences were observed between DAPT and tirofiban. Endovascular treatment, particularly SAC, appears to be a safe and feasible option for ruptured AChA aneurysms, with the potential for durable occlusion. However, given the small sample size and exploratory nature of this study, these findings should be considered hypothesis-generating and require confirmation in larger prospective cohorts. Both DAPT and tirofiban appear to be feasible antiplatelet strategies based on the limited data available.